The Newton Model for Seaweed Drying: An Investigation of a Cabinet Dryer Using Biomass Energy - Apriandi, Nanang; Herlambang, Yusuf Dewantoro; Khoryanton, Ampala; Safarudin, Yanuar Mahfudz; Widya Baskara, Zulhan; Raharjanti, Rani; Zulhan Widya Baskara (Politeknik Negeri Semarang, 2023)
This study investigates the viability of employing a cabinet-type dryer with a heat energy source derived from biomass combustion to dry Eucheuma sp. using Newton's model. In this investigation, seaweed was dried with air at a temperature of 55 °C. A reduction in water content of 8.1% was attained after six hours of drying. To make the data fit the suggested drying mathematical model, the data were examined and recorded. The model feasibility test shows that, with a coefficient of determination (R2) that is close to one and corrected at 0.9502, the Newton model can be used to predict the moisture content of dried seaweed after the drying process using a cabinet-type dryer with a source of heat energy from biomass combustion.